Control and management in a complex biotechnical system of a dairy farm - V. V. Kirsanov; R. A. Baisheva (Аграрная наука Евро-Северо-Востока, 2020)
The research is aimed at profound study of the influence of the "machine" factor (M) in the "human-machineanimal" system ("H-M-A") with the detailed description of the functions performed by "M", taking into account the convey of "M" control and control functions from the subsystems "human-operator" (HO) and "animal" (A). The paper presents the scheme of transformation and expansion of machine functionality in a biotechnical system; mathematical modeling of the dependence of technological signals controlled by the functions of local biotechnological systems (LBTS); mathematical model of diagnostic signals about the corresponding parameters of technical blocks of LBTS. Algorithmization and digitalization of processes on a dairy farm include an extended list of control indicators: technological signals, diagnostic signals and "alarm" signals presented in the article in matrix form. Monitoring the parameters of the most important subsystem "M" of the complex biotechnical system "H-M-A" of a dairy farm provides an increase in the level of automation, digitalization and intellectualization of the corresponding processes of milking, feeding, manure removal and others which creates prerequisites for improving their work and servicing animals as well as increasing the level of autonomy of their functioning. The development of the "machine" factor of the system is advisable on the basis of the machine-centric model of the LBTS, which will gradually expand its functions due to the transferred control and management functions from the corresponding subsystems "HO" and "A". The control parameters are determined at the characteristic reference points of the quarter curves of milk output for the development of refined algorithms for controlling the milking processes of individual udder shares in automated and robotic milking machines of the new generation. A graphical and numerical model of a wheeled feed-pusher robot in the Matlab/Simulink environment is shown. The created mathematical model of motion control by a wheeled feed-pusher robot provides effective interaction of the positioning system and the wheeedl robot drive in digital of autonomous movement.